2020
DOI: 10.21037/cdt-20-711
|View full text |Cite
|
Sign up to set email alerts
|

Determining the thresholds for abnormal left ventricular strains in healthy subjects by echocardiography: a meta-analysis

Abstract: Background: Left ventricular global longitudinal strain (LVGLS), circumferential strain (LVGCS) and radial strain (LVGRS) are echocardiographic parameters with wide clinical applicability. However, the thresholds for abnormal left ventricular (LV) strains, particularly the lower limits of normal (LLN), are not well established. This meta-analysis determined the mean and LLN of two-(2D) and three-dimensional (3D)LV strain in healthy subjects and factors that influence strain measurements.Methods: We searched Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Based on the mean and LLN with their SD or SE, meta-analysis was performed using the DerSimonian-Laird method random effects models to estimate pooled RV strain parameter means and LLNs with 95%CIs, and Forest Plots presented in all eligible studies reporting the RV strain parameters analyzed [9,10]. These analyses were also performed for purpose of sensitivity analysis performed for cohort studies of healthy subjects only and excluding case-controlled studies, and performed separately by strain vendor software if reported in at least 2 studies due to presumptive differences.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the mean and LLN with their SD or SE, meta-analysis was performed using the DerSimonian-Laird method random effects models to estimate pooled RV strain parameter means and LLNs with 95%CIs, and Forest Plots presented in all eligible studies reporting the RV strain parameters analyzed [9,10]. These analyses were also performed for purpose of sensitivity analysis performed for cohort studies of healthy subjects only and excluding case-controlled studies, and performed separately by strain vendor software if reported in at least 2 studies due to presumptive differences.…”
Section: Methodsmentioning
confidence: 99%
“…The pooled LLNs and their respective 95%CIs reported in this study, rather than the pooled means, are necessary to defining reference ranges [9,10]. The 95%CI of LLN reflects the range…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…The implications are that biomarker values should not have a binary interpretation of normal or abnormal but should be categorized into 3 groups. 4 Measurements within the 95% CI of the LRV or URV are deemed borderline because it is uncertain whether the measurement is above or below the true LRV or URV. Measurements outside the 95% CI and closer to the mean are considered normal, and measurements outside the 95% CI and further from the mean are considered abnormal.…”
mentioning
confidence: 99%